Effects of SAQ Training on Ball Possession Ability of Thailand’s Leading Futsal Athletes - Nualwichit, Purachet; Choeychom, Kongkiat (Interdisciplinary Academic and Research Journal, 2023)
Futsal is a sport that moves, moves, changes position almost all the time in the game, especially at short speeds that require rapid changes in direction of movement, and it’s not just once or twice but it’s the player’s practice in the game most of the time. Also known as SAQ, it is a popular practice among athletes, from school sports kids to professional athletes alike benefiting from SAQ training. Athletes with good speed and agility will have an advantage over their opponents in sports competitions because futsal moves quickly and changes direction all the time. Thus, the purposes of this research were to study and compare the effects of SAQ training on the ball possession ability of Thai elite futsal athletes before training, after the fourth week of training, and after the eighth week of training. The participants were 20 futsal athletes from Nonthaburi Futsal Club. They were assigned to either the experimental group (n= 10) or the control group (n=10). Training according to the SAQ training program designed by the researcher was conducted 3 days per week (Monday, Wednesday, and Friday) from 6.00 p.m. to 8.00 p.m. for 8 weeks. Statistical data analysis consisted of mean, standard deviation, one-way repeated measures ANOVA, and t-test. The findings revealed that there was no significant difference in ball possession ability between the experimental and control groups before training, while statistically significant differences in ball possession ability were found between the two groups after the fourth and eighth weeks of training at a significance level of 0.05.